Cultural and Religious Diversity in Early Childhood Education and Care (ECEC) Teams.: Potentials of Diverse Teacher Teams for Inclusive Learning Environments - Hofmann, Julia; Boschki, Reinhold; Knoblauch, Christoph (Österreichisches Religionspädagogisches Forum, 2025)
This paper investigates the role of cultural and religious diversity within Early Childhood Education and Care (ECEC) teams. Through an explorative meta-analysis of international research on diversity in educational teams, the paper explores the significance of diversity in ECEC settings, aligning with national and international educational plans. It addresses challenges related to cultural and religious diversity within ECEC teams and suggests potential approaches to leverage diversity for enhancing inclusivity. Through a review of empirical studies, the paper identifies practical strategies for effectively managing cultural and religious diversity in early childhood settings.